Rootstocks increase grapevine tolerance to NaCl through ion compartmentalization and exclusion - Martin, Leandro Damián (2020)
The productivity of Vitis vinifera L. is limited by salinity, especially under water and drainage deficits, and could aggravate with climate change. The use of tolerant rootstocks is a strategy against salinity that helps yield maintenance. Some Argentinean grapevine cultivars show tolerance to salinity, although the mechanisms are yet unknown. The physiology of Malbec vines was evaluated with 4 V. vinifera rootstocks: Torrontés Riojano (TR) and Torrontés Sanjuanino (TS) Argentine varieties, and the hybrids 3309 Courdec (3309C, salinity sensitive) and 1103 Paulsen (1103P, tolerant), submitted to NaCl 0, 50 or 100 mM during 65 days. Mild and high salinity levels reduced vegetative growth (50 and 70%, respectively), photosynthesis and leaf water content. Midday ΨL reached − 1.16 MPa (moderate water stress) with 100 mM NaCl, which expressed as oxidative damage in mature leaves, thus affecting protein content, membrane integrity and lipid peroxidation. Proline accumulation in leaves increased in 1103P and TR under 50 mM, while 1103P showed the highest value in 100 mM NaCl. An increased vegetative expression and vigor were induced by TS. Accumulation of Na+ and Cl− ions in roots was found in TR and TS, suggesting a compartmentalization strategy, while 1103P excluded them.